MEKTEPLERDE TÁLIM SISTEMASÍN RAWAJLANDÍRÍW PROGRAMMASÍNÍŃ ANALIZI - Abdullaeva, R.A. (SCIENCE and SOCIETY, 2023)
This article supplements the types of educational institutions, the structure of modern innovative education, the specifics of innovative processes in education, as a factor contributing to innovation in modern education.